Antecedents of loyalty to bank: The role of trust in cryptocurrency and concern in investing - Alifia, Athalla Destya; Rafik, Abdur (Universitas Ahmad Dahlan, 2024)
In recent years, cryptocurrency has become a topic frequently discussed by investors. Cryptocurrency is a type of digital money that was first intended to be used as a medium of exchange but has since evolved into an investment tool. This study examines the influence of cryptocurrency knowledge, trust in government, transaction speed, and herding behavior on trust in cryptocurrency. The impact of trust in cryptocurrency on concern about investing, the influence of trust in cryptocurrency on loyalty to banks, the influence of concern about investing on loyalty to banks, and the impact of trust in cryptocurrency on loyalty to banks mediated by concern about investing. The research respondents were from the general public, who knew about cryptocurrency, totaling 200 respondents. This study used a purposive sampling technique via Smart PLS. The results of this research show that cryptocurrency knowledge, transaction speed, and herding behavior positively affect trust in cryptocurrencies. By contrast, trust in the government does not significantly affect trust in cryptocurrencies. Trust in cryptocurrency has a negative effect on concern about investing, trust in cryptocurrency has a negative impact on loyalty to the bank, concern about investing has a positive effect on loyalty to the bank, and concern about investing mediates between trust in cryptocurrency and loyalty to the bank.